Inovasi Pelayanan Publik dalam Pendampingan Ekonomi Kreatif di Kampung Wisata Anyer Desa Tambang Ayam Kabupaten Serang - Nindi Riyan Gustin; Zakaria Habib Al-Ra'zie; Yulvia Chrisdiana (Lembaga Pengembangan Kinerja Dosen, 2026)
The Tambang Ayam Village Tourism Village in Serang Regency has great potential for community-based tourism and halal tourism development. However, this area still faces various challenges such as limited tourism information systems, suboptimal coordination between stakeholders, and unprofessional management of creative economy products. This community service activity aims to provide the community and village officials with an understanding of public service innovations and creative economy assistance in supporting the development of the tourism village. The implementation method includes an initial survey, community service, and outreach. The activity was held on July 26, 2025, at the Tambang Ayam Village Hall, with 70 residents in attendance. The results of the activity demonstrated high community enthusiasm, marked by active participation in discussions and questions and answers. In addition to outreach, the activity also included the provision of cooking equipment to support the creative economy and free health checks for residents. Through this activity, it is hoped that the tourism village can develop into a competitive and sustainable tourist destination.